EFEKTIVITAS PENGESAHAN SURAT TANDA NOMOR KENDARAAN (STNK) MELALUI SAMSAT DRIVE THRU BADUNG BERDASARKAN PERATURAN KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 7 TAHUN 2021 - Andika, I Kadek Roi (Kerta Dyatmika, 2024)
The validation of the Vehicle Registration Certificate (STNK) is a mandatory annual obligation as stipulated in the Regulation of the Chief of the Indonesian National Police Number 7 of 2021 concerning the Registration and Identification of Motor Vehicles, and Law Number 22 of 2009 concerning Road Traffic and Transportation. To enhance public service delivery, the Samsat Drive Thru system was introduced as an innovative mechanism. However, its implementation still faces several challenges, as evidenced by the considerable number of citizens who fail to fulfill their STNK validation obligations. This study aims to analyze the effectiveness of STNK validation through the Samsat Drive Thru in Badung, and to identify the obstacles and efforts made by the police in enforcing such validation in accordance with applicable regulations. This is an empirical legal research with a descriptive approach, employing the principles of legality, the concept of effectiveness, and the theory of law enforcement. Data collection was conducted through triangulation methods, including observation, interviews, and document studies, and subsequently analyzed using qualitative methods. The findings reveal that the effectiveness of STNK validation through the Samsat Drive Thru in Badung when assessed through indicators of goal achievement, adaptation, and integration still requires optimization. Identified obstacles include legal factors, law enforcement personnel, public awareness, and infrastructure limitations. Police efforts to address these challenges include implementing legally compliant policies, enhancing public outreach, improving personnel competence, upgrading facilities, and conducting continuous monitoring and evaluation. The study concludes that although there has been progress, further optimization is necessary to ensure more effective STNK validation through the Samsat Drive Thru mechanism.